The Relationship between Academic Achievement at Undergraduate Stage and Professional Stage with Objective Competency Test Scores Structured Clinical Examination ( OSCE ): Study of Abdurrab University Medical Students - Susiana Anggraini; Ikhsan Julian; Huda Marlinawati (International Journal of Education and Literature, 2024)
Objective Structured Clinical Examination (OSCE) is a form of competency test which aims to ensure that psychomotor abilities and skills are in accordance with doctor competency standards . This exam is taken by all prospective doctors who have completed undergraduate and professional education , marked by achieving a Cumulative Achievement Index (GPA). The 2018 OSCE Medical Professional Program Students Competency Test (UKMPPD) results experienced a decline compared to the previous year . The decrease in the UKMPPD OSCE pass rates is one of the evaluation materials for the students learning process at both undergraduate and professional stages . To find out whether there is a relationship between undergraduate and professional GPA with UKMPPD OSCE scores at Abdurrab Universities. This research uses an observational study design with a Retrospective Cohorts analytical approaches.The research was conducted on Abdurrab University students who had taken the OSCE UKMPPD. The sampling technique is a total sampling technique with references to the first participants . Data were analyzed using the Spearman Rank correlation test. There is a significant relationships between undergraduate GPA and professional level GPA (p- value 0.00), correlation coefficient 0.56. There is a significant relationships between undergraduate GPA and UKMPPD OSCE scores (p- value = 0.00), correlation coefficient 0.54. There is a relationship between professional stage GPA and UKMPPD OSCE scores (p- value = 0.00), correlation coefficient 0.34. Furthermore , there is a significant relationships between the length of study period at the undergraduate and professional stages and passing the UKMPPD OSCE (p- value 0.00) and a correlation coefficient of -0.37 and -0.25. Cumulative Achievement Index (GPA) at undergraduate and professional levels can be used as a reference for passing UKMPPD OSCE.